High‐ionicity fluorophosphate lattice via aliovalent substitution as advanced cathode materials in sodium‐ion batteries. Issue 6 (31st March 2021) - Gu, Zhen‐Yi; Guo, Jin‐Zhi; Zhao, Xin‐Xin; Wang, Xiao‐Tong; Xie, Dan; Sun, Zhong‐Hui; Zhao, Chen‐De; Liang, Hao‐Jie; Li, Wen‐Hao; Wu, Xing‐Long
Abstract: As a cathode for sodium‐ion batteries (SIBs), Na3 V2 (PO4 )2 F3 (NVPF) with 3D open framework is a promising candidate due to its high working voltage and large theoretical capacity. However, the severe capacity degradation and poor rate capability hinder its practical applications. The present study demonstrated the optimization of Na‐storage performance of NVPF via delicate lattice modulation. Aliovalent substitution of V 3+ at Na + in NVPF induces the generation of electronic defects and expansion of Na + ‐migration channels, resulting in the enhancement in electronic conductivity and acceleration of Na + ‐migration kinetics. It is disclosed that the formed stronger NaO bonds with high ionicity than VO bonds lead to the significant increase in structural stability and ionicity in the Na + ‐substituted NVPF (NVPF‐Nax ). The aforementioned effects of Na + substitution achieve the unprecedented electrochemical performance in the optimized Na3.14 V1.93 Na0.07 (PO4 )2 F3 (NVPF‐Na0.07 ). As a result, NVPF‐Na0.07 delivers a high‐rate capability (77.5 mAh g −1 at 20 C) and ultralong cycle life (only 0.027% capacity decay per cycle over 1000 cycles at 10 C). Sodium‐ion full cells are designed using NVPF‐Na0.07 as cathode and Se@reduced graphene oxide as anode. The full cells exhibit excellent wide‐temperature electrochemical performance from −25 to 25°C with an outstanding rate capability (96.3 mAh g −1 at 20 C). Furthermore, it delivered an excellent cycling performance over 300 cycles with a capacity retention exceeding 90% at 0.5 C under different temperatures. This study demonstrates a feasible strategy for the development of advanced cathode materials with excellent electrochemical properties to achieve high‐efficiency energy storage. Abstract : An advanced Na3.14 V1.93 Na0.07 (PO4 )2 F3 cathode with high ionicity and excellent energy‐storage performance is prepared via aliovalent substitution of V 3+ at Na + sites. It exhibits the higher structural stability and improved electron/ion‐transport kinetics than the pristine Na3 V2 (PO4 )2 F3 owing to the stronger NaO and VO bonds, thereby extending the cycle life of NASICON cathode materials.